Combined bulk RNA-seq and single-cell RNA-seq identifies a necroptosis-related prognostic signature associated with inhibitory immune microenvironment in glioma - Wan, Sicheng; Moure, Ulrich Aymard Ekomi; Liu, Ruochen; Liu, Chaolong; Wang, Kun; Deng, Longfei; Liang, Ping; Cui, Hongjuan (Frontiers in Immunology, 2022)
Necroptosis is a programmed cell death playing a significant role in cancer. Although necroptosis has been related to tumor immune environment (TIME) remodeling and cancer prognosis, however, the role of necroptosis-related genes (NRGs) in glioma is still elusive. In this study, a total of 159 NRGs were obtained, and parameters such as mutation rate, copy number variation (CNV), and relative expression level were assessed. Then, we constructed an 18-NRGs-based prognostic signature (NRS) in the TCGA dataset, which could predict the patient's prognosis and was validated in two external CGGA datasets. We also explored the correlation between NRS and glioma TIME, chemotherapy sensitivity, and certain immunotherapy-related factors and molecules. The two necroptosis-related subtypes were discovered and could can also distinguish the patients prognosis. Through the glioblastoma (GBM) scRNA-seq data analysis, NRGs’ expression levels in different GBM patient tissue cell subsets were investigated and the relative necroptosis status of different cell subsets was assessed, with the microglia score culminating among all. Subsequent experiments were performed in human glioma cell lines to verify analytic findings. Moreover, we found a high infiltration level of immunosuppressive cells in glioma TIME, which is associated with poor prognosis in the high-NRS glioma patient group. Finally, the necroptosis suppressor CASP8 exhibited a high expression in glioma and was associated with poor prognosis. Altogether, this study provides comprehensive evidence revealing a prognostic value of NRGs in glioma, which is associated with TIME regulation.